Reporting Achievement of Medical Student Milestones to Residency Program Directors: An Educational Handover. (May 2016) - Sozener, Cemal B.; Lypson, Monica L.; House, Joseph B.; Hopson, Laura R.; Dooley-Hash, Suzanne L.; Hauff, Samantha; Eddy, Mary; Fischer, Jonathan P.; Santen, Sally A.
Abstract : Problem: Competency-based education, including assessment of specialty-specific milestones, has become the dominant medical education paradigm; however, how to determine baseline competency of entering interns is unclear—as is to whom this responsibility falls. Medical schools should take responsibility for providing residency programs with accurate, competency-based assessments of their graduates. Approach: A University of Michigan ad hoc committee developed (spring 2013) a post-Match, milestone-based medical student performance evaluation for seven students matched into emergency medicine (EM) residencies. The committee determined EM milestone levels for each student based on assessments from the EM clerkship, end-of-third-year multistation standardized patient exam, EM boot camp elective, and other medical school data. Outcomes: In this feasibility study, the committee assessed nearly all 23 EM milestones for all seven graduates, shared these performance evaluations with the program director (PD) where each student matched, and subsequently surveyed the PDs regarding this pilot. Of the five responding PDs, none reported using the traditional medical student performance evaluation to customize training, four (80%) indicated that the proposed assessment provided novel information, and 100% answered that the assessment would be useful for all incoming trainees. Next Steps: An EM milestone-based, post-Match assessment that uses existing assessment data is feasible and may be effective for communicating competency-based information about medical school graduates to receiving residency programs. Next steps include further aligning assessments with competencies, determining the benefit of such an assessment for other specialties, and articulating the national need for an effective educational handover tool between undergraduate and graduate medical education institutions.